2006
DOI: 10.1295/polymj.pj2005211
|View full text |Cite
|
Sign up to set email alerts
|

Application of Catastrophe Theory to the Neck-initiation of Semicrystalline Polymers Induced by the Intercluster Links

Abstract: ABSTRACT:This paper deals with the neck initiation in semi-crystalline polymers having lamellar clusters connected by the intercluster links composed of extended-chain bundles as demonstrated by electron microscope pictures of polyethylene and polypropylene. When semicrystalline polymers are uniaxially deformed at a constant rate, the necking is usually initiated and the necking zone propagates at a constant speed along the sample specimen. The necking initiation is explained in this paper by a first order cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 44 publications
0
16
0
Order By: Relevance
“…4. The first yield because of initiation of the collapse of spherulites and the second yield because of the onset of neck formation [31][32][33][34] are clearly observed at ε ≈ 0.6 and ε ≈…”
Section: Resultsmentioning
confidence: 99%
“…4. The first yield because of initiation of the collapse of spherulites and the second yield because of the onset of neck formation [31][32][33][34] are clearly observed at ε ≈ 0.6 and ε ≈…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the authors mainly focused at the post‐yield strain domain without considering the plastic instability phenomenon and the natural draw ratio. More recently, Nitta and Takayanagi76 tackled the problem of the plastic instability onset through the catastrophic theory. This approach, unfortunately, does not consider the occurrence of the natural draw ratio.…”
Section: Theoretical Approaches To the Natural Draw Ratiomentioning
confidence: 99%
“…Kilian et al 14,15 showed that the constitutive relation of semicrystalline polymers can be expressed by the extension of the ideal gas model to the van der Waals equation where bulky fragmented lamellar clusters are assumed to behave as junction points. 16 Based on these excellent theoretical considerations, Nitta-Takayanagi 17 explained the initiation of a neck by the mathematical fact that the van der Waals equation shows a first-order catastrophic phase transition. In this work, we apply the catastrophe theory to the initiation of necking in a metallocene-catalyzed HDPE.…”
Section: Introductionmentioning
confidence: 99%